Copy number variation plays an important role in clinical epilepsy. Issue 6 (13th June 2014) - Olson, Heather; Shen, Yiping; Avallone, Jennifer; Sheidley, Beth R.; Pinsky, Rebecca; Bergin, Ann M.; Berry, Gerard T.; Duffy, Frank H.; Eksioglu, Yaman; Harris, David J.; Hisama, Fuki M.; Ho, Eugenia; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the role of copy number abnormalities detectable using chromosomal microarray (CMA) testing in patients with epilepsy at a tertiary care center. Methods We identified patients with International Classification of Diseases, ninth revision (ICD‐9) codes for epilepsy or seizures and clinical CMA testing performed between October 2006 and February 2011 at Boston Children's Hospital. We reviewed medical records and included patients who met criteria for epilepsy. We phenotypically characterized patients with epilepsy‐associated abnormalities on CMA. Results Of 973 patients who had CMA and ICD‐9 codes for epilepsy or seizures, 805 patients satisfied criteria for epilepsy. We observed 437 copy number variants (CNVs) in 323 patients (1–4 per patient), including 185 (42%) deletions and 252 (58%) duplications. Forty (9%) were confirmed de novo, 186 (43%) were inherited, and parental data were unavailable for 211 (48%). Excluding full chromosome trisomies, CNV size ranged from 18kb to 142Mb, and 34% were >500kb. In at least 40 cases (5%), the epilepsy phenotype was explained by a CNV, including 29 patients with epilepsy‐associated syndromes and 11 with likely disease‐associated CNVs involving epilepsy genes or "hotspots." We observed numerous recurrent CNVs including 10 involving loss or gain of Xp22.31, a region described in patients with and without epilepsy. Interpretation Copy number abnormalities play an important role in patients with epilepsy. Because the diagnostic yield of CMA for epilepsy patients is similar to the yield in autism spectrum disorders and in prenatal diagnosis, for which published guidelines recommend testing with CMA, we recommend the implementation of CMA in the evaluation of unexplained epilepsy. Ann Neurol 2014;75:943–958